Plasmon-Enhanced Scattering and Fluorescence Used for Ultrasensitive Detection in Langmuir-Blodgett Monolayers - Volpati, Diogo [UNESP]; Alsaleh, Aisha; Constantino, Carlos J.L. [UNESP]; Aroca, Ricardo (Wiley, 2014)
The artificial bilayer structures of lipids and phospholipids can be fabricated using the Langmuir-Blodgett (LB) technique. High sensitivity and ultrasensitive detection can only be achieved using plasmon-enhanced spectroscopy, such as surface-enhanced Raman scattering (SERS). This chapter describes the single molecule detection of tagged-phospholipids using the LB technique and plasmon-enhanced scattering. It explores the plasmon-enhanced fluorescence using the LB technique and silver and gold shell-isolated nanoparticles (SHINs). The chapter examines the silver and gold SHIN enhanced fluorescence (SHINEF) results obtained in solution, by casting, and the formation of a two-dimensional SHINs surface to be used, in SHINEF experiments.
Keywords: Langmuir-Blodgett (LB) technique; Plasmon-enhanced fluorescence; Plasmon-enhanced scattering; Shell-isolated nanoparticle enhanced fluorescence (SHINEF); Surface-enhanced Raman scattering (SERS); Tagged phospholipids; Ultrasensitive detection